Penerapan Algoritma Base64 untuk Enkripsi dan Dekripsi File Gambar - Dominikus S Bani; Andreas Ariyanto Rangga; Dian Fransiska Ledi (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2024)
Along with the development of the times, the use of information technology using computers as its media has increased rapidly. Indonesia is currently starting to adopt the concept of society 5.0 or what is known as Society 5.0, where this kind of activity focuses on community settings that are oriented towards IT-based human activities (Wijayanti et al., 2022). The application of the concept of "society 5.0" has brought many technological advances in various fields of life that are connected to the internet, especially in Indonesia. The base64 technique produces values ​​during text encoding that are difficult for laypeople to understand. This encryption program has the ability to convert plain text to cipher text and reverse cipher text after it is received. Several recommendations for the development of better applications in further research can be made based on the test findings of this study and the conclusions mentioned above. These include the following: The Vigenere Chipper application can only encrypt text messages